1998
DOI: 10.1017/s0952523898152069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bicarbonate versus HEPES buffering on measured properties of neurons in the salamander retina

Abstract: Electrophysiological studies of the isolated retina involve perfusing the tissue with a physiological Ringer's. Organic pH buffers such as HEPES have become increasingly popular in recent years because for many purposes they offer a convenient and reliable alternative to the more traditional bicarbonate/CO2. In this paper, however, we report that important functional properties of rods, bipolar cells, and horizontal cells in the salamander, Ambystoma tigrinum, are sensitive to the choice of buffer and, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…HEPES increased the light response amplitude and receptive field size of horizontal cells, consistent with a previous study (Hare and Owen, 1998) in which the normal bicarbonate buffer was replaced with HEPES. It was hypothesized that, because HEPES cannot cross cell membranes, unlike bicarbonate, intracellular pH regulation was perturbed causing the observed changes in retinal physiology.…”
Section: H1 Horizontal Cellssupporting
confidence: 77%
“…HEPES increased the light response amplitude and receptive field size of horizontal cells, consistent with a previous study (Hare and Owen, 1998) in which the normal bicarbonate buffer was replaced with HEPES. It was hypothesized that, because HEPES cannot cross cell membranes, unlike bicarbonate, intracellular pH regulation was perturbed causing the observed changes in retinal physiology.…”
Section: H1 Horizontal Cellssupporting
confidence: 77%
“…In these cells, rollback returned (5 Ϯ 2 and 8 Ϯ 2% of peak hyperpolarizing response) after HEPES (n ϭ 3) and Tris (n ϭ 5), respectively. Hare and Owen (1998) found that the amplitude of horizontal cell light responses was dramatically increased when bicarbonate buffers were replaced with HEPES (pH 7.8) and that the cells depolarized by ϳ30 mV in addition to other effects, consistent with cytoplasmic alkalinization. In contrast, we added HEPES to the bicarbonate-buffered saline, and we did not observe such large changes in the light response.…”
Section: Proton Buffering Reduces the Feedback Response Of Horizontalmentioning
confidence: 88%
“…In the present study, the main mechanism regulating cytosolic acid loads under nominally bicarbonatefree conditions was the ubiquitous electroneutral Na ϩ /H ϩ antiporter, which couples proton transport to the sodium gradient (34,59). Vertebrate photoreceptors may also express electroneutral Cl Ϫ /HCO 3 Ϫ exchange (28,34,38,59) and electrogenic Na ϩ -HCO 3 Ϫ cotransport and Na ϩ -driven C Ϫ /HCO 3 Ϫ exchange mechanisms (10,83), which could be functionally coupled to carbonic anhydrases within the bicarbonate transport metabolon (62). It is likely that addition of bicarbonate and activation of cytosolic and extracellular carbonic anhydrases has additional effects on photoreceptor pH i and [Ca 2ϩ ] i regulation, outer retinal feedback, and photoreceptor cell death (10,23,83).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the blood acid-base balance in ectothermic amphibians such as Ambystoma suggest that the concentration of bicarbonate in arterial blood can vary widely over the physiological temperature range of 5 to 25°C (13a, 14a). Hence, HEPES has typically been the buffer of choice in studies that characterized pH, chloride, and calcium signaling mechanisms in isolated photoreceptors (3-4, 17, 34, 37, 39 -41, 50, 55, 60, 63-66, 68 -69) and horizontal cells (67) and has also been used in investigations of synaptic transmission at photoreceptor synapses (28,37). In the present study, the main mechanism regulating cytosolic acid loads under nominally bicarbonatefree conditions was the ubiquitous electroneutral Na ϩ /H ϩ antiporter, which couples proton transport to the sodium gradient (34,59).…”
Section: Discussionmentioning
confidence: 99%